Antigen gene and variable number tandem repeat (VNTR) diversity in Theileria parva parasites from Ankole cattle in south‐western Uganda: Evidence for conservation in antigen gene sequences combined with extensive polymorphism at VNTR loci. (16th March 2020) - Nanteza, Anne; Obara, Isaiah; Kasaija, Paul; Mwega, Elisa; Kabi, Fredrick; Salih, Diaeldin A.; Njahira, Moses; Njuguna, Joyce; Odongo, David; Bishop, Richard P.; Skilton, Rob A.; Ahmed, Jabbar; et al.
Abstract: Theileria parva is a tick‐transmitted apicomplexan protozoan parasite that infects lymphocytes of cattle and African Cape buffalo ( Syncerus caffer ), causing a frequently fatal disease of cattle in eastern, central and southern Africa. A live vaccination procedure, known as infection and treatment method (ITM), the most frequently used version of which comprises the Muguga, Serengeti‐transformed and Kiambu 5 stocks of T. parva, delivered as a trivalent cocktail, is generally effective. However, it does not always induce 100% protection against heterologous parasite challenge. Knowledge of the genetic diversity of T. parva in target cattle populations is therefore important prior to extensive vaccine deployment. This study investigated the extent of genetic diversity within T. parva field isolates derived from Ankole ( Bos taurus ) cattle in south‐western Uganda using 14 variable number tandem repeat (VNTR) satellite loci and the sequences of two antigen‐encoding genes that are targets of CD8+T‐cell responses induced by ITM, designated Tp1 and Tp2. The findings revealed a T. parva prevalence of 51% confirming endemicity of the parasite in south‐western Uganda. Cattle‐derived T. parva VNTR genotypes revealed a high degree of polymorphism. However, all of the T. parva Tp1 and Tp2 alleles identified in this study have been reported previously, indicating that they are widespread geographically in East Africa and highly conserved.